Dynamics of Muktazilah Theological Thought - Nabil Amir, Ahmad; Tasmin Abdul Rahman (Asketik: Jurnal Agama dan Perubahan Sosial, 2025)
The paper examines historical development of Mu‘tazilite theological school of thought which arises from speculative method and influences of Greek thought that sparked the discursive tradition of early Islamic intellectual history. This essentially brought forth by the textualist and rationalist school and their classical debate that had formative influence in the rational school developed by the Mu‘tazilite in the early century. The paper studies the history and development of Mu‘tazilite theology and their conceptual and doctrinal impact on modern neo-Mu‘tazilite works. The study is based on classical works that gives significant textual and interpretive history of Mu‘tazilism. It uses qualitative method based on documentary survey and content analysis. The data were collected from related primary and secondary sources and analyzed using descriptive, normative, historical and jurisdictional approaches in order to make accurate and scientific conclusions. The finding shows that the ideology developed by the Mu‘tazilite were meant to respond to the foreign influence of deviant sects of the heretics, Magians, Manichaeism, atheism, naturalist and materialist by refuting their philosophical premises. This contributes to the development of kalam or speculative theology thanks to the flowering of Mu‘tazilite theology and their rational expression that help to foster higher ethical and religious norms and consciousness and influences contemporary thought that espouses neo-Mu‘tazilite outlook in the context of dakwah and the return to reason and their enlightened movement.